Optimization Of Blended Learning With Google Classroom Towards Increasing Students' Learning Outcomes In Relationship Materials Function Of Class VIII SMPN 1 Sawahlunto Tp. 2020/2021 - Trisia Siska (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Mathematics learning activities at SMPN 1 Sawahlunto during the covid 19 pandemic were previously very weak where only by giving assignments via WA experienced a significant increase by applying blended learning, where students carried out independent learning by participating in learning in google classroom. The average student in class VIII.2 SMPN 1 Sawahlunto at the stage of the second cycle has strongly agreed with blended learning Mathematics with Google Classroom, both in terms of student acceptance on the convenience of Google Classroom and the performance of Google Classroom. Student activity in google classroom in cycle 2 has shown a good average, student activity in answering questions is 66% (good), asking questions 61% (good), Doing activities in LKPD is 62% (good), presentation is 64% (good), opinion is 60% (enough) and writing is 63% (good). Based on the data analysis carried out, it was concluded that learning Mathematics using blended learning with Google Classroom has been running optimally, this is shown by the increase in the results of the evaluation of learning by using the blended learning learning model through Google Classroom with an average of 75.52 and completeness. classic 83%. Observation of the ease of Google Classroom and its performance, more than 50% of students stated strongly agree and agree it was concluded that learning Mathematics using blended learning with Google Classroom was running optimally, this was shown by the increase in the results of the evaluation of learning using the blended learning model through Google Classroom with an average of 75.52 and classical completeness of 83%. Observation of the ease of Google Classroom and its performance, more than 50% of students stated strongly agree and agree it was concluded that learning Mathematics using blended learning with Google Classroom was running optimally, this was shown by the increase in the results of the evaluation of learning using the blended learning model through Google Classroom with an average of 75.52 and classical completeness of 83%. Observation of the ease of Google Classroom and its performance, more than 50% of students stated strongly agree and agree.